A new species and two new records of Tagetes (Asteraceae, Tageteae) from La Rioja province, Argentina - Schiavinato, Dario J.; Bartoli, Adriana (Phytotaxa, 2020)
Tagetes mirandae is described as a new species from La Rioja province in western Argentina. Its distribution area is restricted to Cuesta de Miranda, in the Coronel Felipe Varela department. The new species is closely related to T. pauciloba and T. riojana, but it can be distinguished by morphological characters of inflorescence and florets. We also report two new records from La Rioja province: T. filifolia and T. imbricata.